Efecto de la aplicación del ácido giberélico y la poda para mejorar el rendimiento en el cultivo de naranja (Citrus sinensis O. var Valencia) en Zapotepamba, Provincia de Loja - Valle Castillo, David Vladimir (2023)
Orange (Citrus sinensis O.) is one of the most important crops worldwide. In Ecuador, it is mostly consumed fresh in the local markets of each city, with a national average yield of 10.27 T/ha. in 2020. However, the yield of this crop is locally affected by poor agricultural practices that producers are unaware of, such as pruning, where field research shows a great benefit in improving the quantity and quality of the fruit; in addition, in recent years plant hormones have had a great success in increasing production, due to their importance in the fruiting process for an adequate distribution of nutrients to the fruit. The purpose of the research was to evaluate the effect of the combined application of pruning and gibberellic acid in the improvement of orange yield and quality. The test was carried out on 18 Valencia orange trees, 14 years old and in the same state of production, with a completely randomized block design. The treatments consisted of applying GA3 at the time of petal fall or fruit set with 3 doses of gibberellic acid of 0 ppm, 25 ppm or 50 ppm, on pruned and unpruned plants, forming 6 treatments resulting from the combination of pruning and doses of gibberellin in a bifactorial test. The variables to be measured were flower set, fruit size, fruit weight, number of fruits per tree, yield per plant, soluble solids, pH, acidity, fruit firmness and colorimetry. At the end of the crop, results were obtained that reflected significant values in soluble solids with the highest value of 10.8 °Bx in the treatment without pruning and 50 ppm (T6); as for pH, the highest value of 3.35 was obtained in the treatment with pruning and 0 ppm (T1); finally, in colorimetry in aspect lightness with a value of 81.83 and red/green coordinate with a value of 17.14 in the treatment without pruning and 0 ppm (T4). In addition, there were no significant differences in substantial variables such as fruit set, number, weight, fruit size or yield. It is observed that GA3 has positive effects on soluble solids, pH and colorimetry, although the results could be improved by verifying the amount of doses to be applied if it is desired to repeat the research, modifying the ppm or with a follow up of more years to the study. Key words: Gibberellic acid, pruning, yield, orange, Valencia variety, fruit set, size, weight, soluble solids, pH, acidity, fruit firmness, colorimetry.